Laboratory investigation of the influence of fractures on CO2 flooding - Qing-Fu, Zhang (Frontiers in Earth Science, 2022)
CO2 injection is a promising method for low-permeability reservoirs. CO2 is much easier to inject underground compared with water. The solubility of CO2 in oil decreases the oil density and viscosity, leading to an enhancement of the oil recovery. CO2 flooding could achieve the dual purpose of developing oil effectively and reducing greenhouse gas. Therefore, this technique has both economic and social benefits and is an essential technology for achieving green development. Natural fractures are widely developed in low-permeability reservoirs, and artificial fractures are often used to improve oil development. These fractures have a significant influence on flow patterns during CO2 flooding. In addition, fractures are also one of the key factors of CO2 channeling. Therefore, the influence of fractures on CO2 flooding pressure distribution, fluid composition, and displacement efficiency needs to be studied. In this work, a CO2 flooding experiment was implemented to test the pressure distribution and outlet composition changes during CO2 flooding under different fracture lengths and apertures. The experiment shows that a long and wide fracture could effectively reduce the injection-production pressure difference. However, fractures also had a negative effect on oil development. Fracture length and aperture had a significant effect on the gas phase composition at the outlet, but had little effect on the oil phase composition.